Characterization of colorants and opacifiers in roman glass mosaic tesserae through spectroscopic and spectrometric techniques. (17th February 2014) - Basso, E.; Invernizzi, C.; Malagodi, M.; La Russa, M. F.; Bersani, D.; Lottici, P. P.
<x xml:space="preserve">Abstract</x> Several glass mosaic tesserae were recovered during the archeological excavation of the thermal baths at the 'Villa dei Quintili' in Rome and dated to the second century ad. This work reports the results of an archeometrical investigation performed, through a multi‐technique approach, on 19 colored opaque tesserae. The aims of the study were (1) the characterization of coloring and opacifying agents used for the production of the glass tesserae and (2) the definition of the technological processes involved. Colorimetric measurements allowed us to classify the tesserae in color groups, while the glassy matrix and the dispersed crystallites were characterized in detail through micro‐Raman spectroscopy, field emission scanning electron microscopy with energy dispersive X‐ray spectroscopy, laser ablation‐inductively coupled plasma‐mass spectrometry, and X‐ray powder diffraction analyses. Most of the glass shows the typical soda‐lime‐silicate composition (except for the orange and red tesserae). Raman results and elemental analysis prove the use of Sn–Pb antimonates to create yellow glass and of Ca‐antimonates for the white tesserae. A mixture of Sn–Pb antimonates and copper ions was used to obtain the emerald green color, while Ca‐antimonates were employed in both copper‐colored and cobalt‐colored blue glass to obtain different shades (blue‐green, dark, and light blue). X‐ray powder diffraction analyses reveal the presence of metallic copper (Cu0) and Cu2O particles (cuprite) in red and orange tesserae, respectively. These results confirm the high technological level reached by the glassmakers of the Imperial Age. Copyright © 2014 John Wiley & Sons, Ltd.